Composite wire for anode lead wire of tantalum capacitor and manufacturing method
The composite wire for anode leads in tantalum capacitors, with a core of inexpensive metals or alloys and a tantalum metal layer, addresses the cost issue of tantalum capacitors while maintaining the necessary dielectric properties.
Patent Information
- Application Number
- JP2022553607
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-04-28
- Filing Date
- 2020-10-19
- Publication Date
- 2025-04-23
- Estimated Expiration
- 2040-10-19
AI Technical Summary
The high cost of tantalum and its alloys limits the widespread use of tantalum capacitors, as the current anode lead wires made from pure tantalum or high-tantalum-content alloys are expensive and scarce.
A composite wire for anode leads in tantalum capacitors is developed, featuring a core made of metals or alloys other than pure tantalum, coated with a tantalum metal layer. This design reduces the amount of expensive tantalum required while maintaining the necessary dielectric properties.
The composite wire achieves a high dielectric constant and reliable oxide film formation on the surface, meeting the requirements of tantalum capacitors at a significantly reduced cost.
Smart Images

Figure 0007667580000008 
Figure 0007667580000001 
Figure 0007667580000002
Abstract
Description
[Technical field]
[0001] The present invention relates to the technical field of capacitors, and more particularly to a composite wire for an anode lead of a tantalum capacitor and a method of manufacture thereof. [Background technology]
[0002] Currently, tantalum capacitors are widely used in the fields of communications, computers, automobiles, home appliances, and aerospace. Tantalum capacitors, which are manufactured using tantalum powder as the anode and tantalum wire as the anode lead, have the advantages of small volume, large capacity, easy surface mounting, excellent reliability, and long service life. Therefore, they can operate stably under harsh conditions where many other capacitors (such as ceramic and aluminum thin film capacitors) are not suitable.
[0003] However, tantalum is a rare metal, and resources are scarce, difficult to extract and smelt, and expensive. If pure tantalum or an alloy with a high tantalum content is used as an anode lead wire, a high dielectric constant and highly reliable oxide film formed by anodization on the surface of the anode lead wire can be ensured. However, tantalum metal is expensive, and the high cost also greatly limits its application fields and scope.
[0004] Therefore, there is an urgent need to develop an anode lead that is relatively low in cost but has a dielectric constant that meets the requirements of tantalum capacitors. Summary of the Invention [Problem to be solved by the invention]
[0005] SUMMARY OF THE PRESENT EMBODIMENT The present invention aims to provide a composite wire for an anode lead of a tantalum capacitor and a manufacturing method thereof, so as to provide an anode lead having a relatively low cost but a dielectric constant that can meet the requirements of the tantalum capacitor. [Means for solving the problem]
[0006] In order to achieve the above object, one aspect of the present invention provides a composite wire for an anode lead of a tantalum capacitor, the composite wire for an anode lead of a tantalum capacitor comprising a core made of a metal other than pure tantalum, or a tantalum alloy or other metal alloy, and a tantalum metal layer coating the outer surface of the core.
[0007] Furthermore, when the material of the tantalum metal layer is a tantalum-niobium alloy, the tantalum content is greater than 50% and the sum of the tantalum and niobium contents is greater than 95%; when the material of the tantalum metal layer is an alloy other than a tantalum-niobium alloy, the tantalum content is greater than 95%.
[0008] Furthermore, the cross section of the composite wire for the anode lead of a tantalum capacitor may be circular, elliptical, or polygonal.
[0009] Furthermore, the proportion of the cross-sectional area of the tantalum metal layer in the cross-sectional area of the composite wire for an anode lead of a tantalum capacitor is in the range of 1% to 80%, and preferably 1 to 50%.
[0010] Further, the cross section of the composite wire is axially symmetrical, with the longest axis being ≦3.0 mm and the shortest axis being ≧0.1 mm.
[0011] Furthermore, the material of the core is one or more selected from the group consisting of niobium, zirconium, tungsten, molybdenum, titanium, nickel, iron, copper, aluminum, magnesium, cobalt, and alloys thereof.
[0012] According to one aspect of the present invention, there is provided a method for producing a composite wire for an anode lead of a tantalum capacitor, the method including a step S1 of providing a core, and a step S2 of coating an outer surface of the core with a tantalum metal layer to obtain a composite wire for an anode lead of a tantalum capacitor.
[0013] In addition, after S2, the method further includes a step of processing the composite wire for the anode lead wire of the tantalum capacitor into a required size by one or more processing methods including extrusion, rolling, rotary swaging, and drawing.
[0014] Furthermore, in S2, the coating of the outer surface of the core with a tantalum metal layer can be achieved by the methods of powder metallurgy, build-up welding, explosive bonding (explosive cladding), pipe dressing cladding or casting cladding, and vapor deposition. Effect of the Invention
[0015] By using the technical solution of the present invention, a composite wire for an anode lead wire of a tantalum capacitor has a core made of a metal other than pure tantalum, or a tantalum alloy or other alloy, and a tantalum metal layer coating the outer surface of the core. In this way, by making full use of the property of the tantalum metal in the surface layer, which allows an oxide film with a high dielectric constant and high reliability to be formed on its surface by anodization, and by filling the core with an inexpensive metal or alloy, the high dielectric constant required for the anode lead wire of a tantalum capacitor is satisfied and costs are significantly reduced. [Brief description of the drawings]
[0016] The drawings in the specification which form a part of this application are used to provide a further understanding of the present invention, and the illustrative embodiments of the present invention and their explanations are used to interpret the present invention and are not intended to unduly limit the present invention.
[0017] [Figure 1] 1 is a schematic diagram showing a cross-sectional structure of a composite wire for an anode lead wire of a tantalum capacitor manufactured according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] In addition, the embodiments and features in the embodiments of the present application may be combined with each other if not inconsistent.The present invention will now be described in detail with reference to the drawings and in conjunction with the embodiments.
[0019] The reason why tantalum wire or high tantalum content alloy wire can be used as the wire material for the anode lead of a tantalum capacitor is mainly because tantalum can form a very thin oxide film on its surface through anodization, which has a high dielectric constant and high reliability. However, the tantalum wire or high tantalum content alloy wire produced by the prior art is expensive, cannot be widely used, or its performance does not meet all the quality requirements of a tantalum capacitor. In response to these technical problems, the present invention proposes the following technical solutions:
[0020] According to an exemplary embodiment of the present invention, there is provided a composite wire for an anode lead of a tantalum capacitor, which includes a core 10 and a tantalum metal layer 20 covering the outer surface of the core, as shown in Figure 1, where the material of the core is a metal other than pure tantalum, or a tantalum alloy or another metal alloy.
[0021] By using the technical solution of the present invention, a composite wire for an anode lead wire of a tantalum capacitor has a core made of a metal other than pure tantalum, or a tantalum alloy or other metal alloy, and a tantalum metal layer coating the outer surface of the core. In this way, by making full use of the property of the tantalum metal in the surface layer, which allows an oxide film with a high dielectric constant and high reliability to be formed on its surface by anodization, and by filling the core with an inexpensive metal or alloy, the high dielectric constant required for the anode lead wire of a tantalum capacitor is satisfied and costs are significantly reduced.
[0022] When the material of the tantalum metal layer is a tantalum-niobium alloy, the tantalum content is greater than 50%, and the sum of the tantalum and niobium contents is greater than 95%; when the material of the tantalum metal layer is an alloy other than a tantalum-niobium alloy, the tantalum content is greater than 95%. Typically, the tantalum content in the tantalum metal layer is 95% or more, so as to ensure that the surface layer of the composite wire for the anode lead of a tantalum capacitor can form an oxide film with a high dielectric constant on its surface by anodization. As for the core, if the tantalum content in the tantalum alloy used is less than 90%, it is sufficient to reduce the cost, and of course, the tantalum content in the tantalum alloy is preferably less than 80%, 70%, or 60%, and more preferably less than 50%, 40%, 30%, 20%, or 10%, etc. In a typical embodiment of the present invention, the material of the core is one or more selected from the group consisting of niobium, zirconium, tungsten, molybdenum, titanium, nickel, iron, copper, aluminum, magnesium, cobalt, and alloys thereof. The cross section of the composite wire for the anode lead of a tantalum capacitor can be set to any shape according to actual needs, such as a circle, an ellipse, or a polygon, where the polygon can be a square, a rectangle, a rhombus, a pentagon, a hexagon, etc.
[0023] In order to fully utilize the performance of tantalum and ensure its excellent performance index without increasing costs too much, the coverage area ratio of the tantalum metal layer is preferably 1% to 80%, and more preferably 1% to 50%; that is, the ratio range of the cross-sectional area of the surface tantalum metal layer to the cross-sectional area of the composite wire for an anode lead of a tantalum capacitor is 1% to 80%, and more preferably 1% to 50%.
[0024] According to an exemplary embodiment of the present invention, the cross section of the composite wire has an axisymmetric shape with a longest axis ≦3.0 mm and a shortest axis ≧0.1 mm.
[0025] In accordance with the invention objectives of the present invention, a tantalum capacitor according to an exemplary embodiment of the present invention is provided, which includes an anode lead wire, and the anode lead wire is made using the composite wire for anode lead wire of a tantalum capacitor of the present invention. Due to the use of the composite wire for anode lead wire of a tantalum capacitor of the present invention, the tantalum capacitor has excellent performance and is significantly reduced in cost.
[0026] According to an exemplary embodiment of the present invention, there is provided a method for manufacturing the composite wire for an anode lead of a tantalum capacitor, comprising the steps of: providing a core (S1); and coating an outer surface of the core with a tantalum metal layer (S2) to obtain a composite wire for an anode lead of a tantalum capacitor.
[0027] In an exemplary embodiment of the present invention, according to actual needs, after S2, the composite wire for the anode lead of the tantalum capacitor may be processed to a required dimension by a method including but not limited to extrusion, rolling, rotary swaging, drawing, etc. However, the coating of the outer surface of the core with a tantalum metal layer in S2 may be achieved by a method including but not limited to powder metallurgy, build-up welding, explosive bonding, tube-shell cladding, or cast cladding.
[0028] The beneficial effects of the present invention will be further described below in conjunction with examples. Example 1 A Ta-40%Nb alloy rod with a diameter of 30 mm and a length of 600 mm is placed in a thin-walled plastic pipe with an inner diameter of 50 mm and a length of 700 mm, one end of which is sealed with a bakelite cap, 3 kg of tantalum powder is placed in the pipe and uniformly distributed around the Ta-40%Nb alloy rod, and the other end is sealed with a bakelite cap. It is isostatically pressed under a pressure of 200 MPa, sintered at 2000°C for 180 minutes under a vacuum of 5×10^-2 Pa or more, isostatically pressed again at 250 MPa, and sintered at 2200°C for 180 minutes under vacuum to obtain a composite rod with an outer diameter of 35 mm.
[0029] This composite rod is rotary swaged to a diameter of 13 mm, pickled, and then annealed by keeping at 1250°C in a vacuum for 60 minutes, rotary swaged again to a diameter of 3 mm, pickled, and then annealed by keeping at 1250°C in a vacuum for 60 minutes, subjected to multi-die drawing (two or more consecutive drawing steps using two or more dies) to a composite wire with a diameter of 1.2 mm, pickled, annealed by keeping at 1250°C in a vacuum for 60 minutes, and subjected to multi-die drawing to a composite wire with a diameter of 0.25 mm.
[0030] Example 2 A Nb-1%Zr alloy rod with a diameter of 30 mm and a length of 600 mm is placed in a thin-walled plastic pipe with an inner diameter of 50 mm and a length of 700 mm. One end is sealed with a bakelite cap, and 3 kg of (95% tantalum powder + 5% niobium powder) is placed in the pipe and uniformly distributed around the Nb-1%Zr alloy rod. The other end is sealed with a bakelite cap. The rod is isostatically pressed under a pressure of 200 MPa, sintered at 2000°C for 180 minutes under a vacuum of 5×10^-2 Pa or more, isostatically pressed again at 250 MPa, and sintered at 2200°C for 180 minutes under vacuum to obtain a composite rod with an outer diameter of 35 mm.
[0031] This composite rod is rotary swaged to a diameter of 13 mm, pickled, and then annealed by keeping at 1250°C for 60 minutes under vacuum, rotary swaged again to a diameter of 3 mm, pickled, and then annealed by keeping at 1250°C for 60 minutes under vacuum, subjected to multi-die drawing to a composite wire with a diameter of 1.2 mm, pickled, annealed by keeping at 1250°C for 60 minutes under vacuum, and subjected to multi-die drawing to a composite wire with a diameter of 0.25 mm.
[0032] Example 3 A tantalum tape that is 1000 mm long, 39 mm wide and 0.5 mm thick is attached to the surface of an SS304 stainless steel rod that is 12 mm in diameter and 1000 mm long, as shown in Figure 1, and the tantalum tape is seam welded by argon arc welding to form a composite rod with an outer diameter of 13 mm. This is then annealed in a vacuum at 1250°C for 180 minutes.
[0033] The subsequent processing of the composite rod with a diameter of 13 mm is the same as that in Example 1, and a composite wire with a diameter of 0.25 mm is finally obtained.
[0034] Example 4 A tantalum tape with a length of 500 mm, width of 78 mm and thickness of 0.5 mm is attached to the surface of a Ta-50%Nb alloy rod with a diameter of 24 mm and a length of 500 mm as shown in Figure 1, and the tantalum tape is seam welded by argon arc welding to form a composite rod with an outer diameter of 25 mm. The rod is then annealed at 1250°C for 180 minutes in a vacuum.
[0035] The subsequent processing of the composite rod with a diameter of 25 mm is the same as that in Example 1, and a composite wire with a diameter of 0.80 mm is finally obtained.
[0036] Example 5 A nickel rod with a diameter of 12 mm and a length of 1000 mm is inserted into a tantalum pipe with an outer diameter of 17 mm, an inner diameter of 12.5 mm and a length of 1000 mm, and annealed at 1250°C for 180 minutes under vacuum to obtain a composite rod with an outer diameter of 17 mm.
[0037] The subsequent processing process of the 17 mm diameter composite rod is the same as in Example 1, to finally obtain a 0.15 mm diameter composite wire.
[0038] Example 6 A nickel rod with a diameter of 10.5 mm and a length of 1000 mm is inserted into a tantalum pipe with an outer diameter of 12 mm, an inner diameter of 11 mm and a length of 1000 mm, and annealed at 1250°C for 180 minutes under vacuum to obtain a composite rod with an outer diameter of 12 mm.
[0039] This composite rod is rotary swaged to a diameter of 3 mm, pickled, and then annealed by holding at 1250°C for 60 minutes under vacuum. It is then multi-die drawn to a composite wire with a diameter of 1.2 mm, pickled, annealed by holding at 1250°C for 60 minutes under vacuum, and rolled in a small multi-roller rolling machine to give a composite flat wire of 1.5 mm x 0.5 mm.
[0040] Example 7 A 65 brass rod with a diameter of 12 mm and a length of 1000 mm is inserted into a tantalum pipe (containing 500 PPM silicon and 200 PPM lanthanum) doped with microcrystalline grains with an outer diameter of 14 mm, an inner diameter of 12.5 mm, and a length of 1000 mm, and annealed at 1250°C for 180 minutes under vacuum to obtain a composite rod with an outer diameter of 14 mm.
[0041] This composite rod is rotary swaged to a diameter of 3 mm, pickled, and then annealed by holding at 1250°C for 60 minutes under vacuum. It is then multi-die drawn to a composite wire with a diameter of 1.2 mm, pickled, annealed by holding at 1250°C for 60 minutes under vacuum, and rolled in a small multi-roller rolling machine to give a composite flat wire of 1.5 mm x 0.5 mm.
[0042] The detection results for the composite wire for the anode lead of the tantalum capacitor and the pure metal tantalum wire produced in Example 1-7 are shown in Table 1-4 below.
[0043] [Table 1]
[0044] [Table 2]
[0045] [Table 3]
[0046] [Table 4]
[0047] In view of the above results, all the detection results of the composite wire meet or exceed the requirements of the Chinese national standard for pure metal tantalum wire (GB / T 26012-2010), which is equivalent to the test level of pure metal tantalum wire.
[0048] The following Tables 5, 6 and 7 show a comparison of the detection results for the composite wires prepared according to the above Examples 1, 2 and 3, and the anode blocks of tantalum capacitors produced by pressing the pure metal tantalum wires with tantalum powder and sintering them.
[0049] [Table 5]
[0050] [Table 6]
[0051] [Table 7]
[0052] In this experiment, composite wire and pure metal tantalum wire were pressed with tantalum powder and sintered to produce anode blocks for tantalum capacitors. The results of wet and dry leakage current detection showed that the test values of the composite wire and pure metal tantalum wire were basically equivalent, and both were superior to or met the requirements of the Chinese national standard (GB / T 2612-2010).
[0053] As can be seen from the above description, the above embodiments of the present invention achieve the following technical effects. 1) The surface of the composite wire manufactured in the above embodiment of the present invention has a high dielectric constant of tantalum, which can meet the requirements for use in tantalum capacitors and has excellent electrical performance. 2) The core part is made of inexpensive metal or alloy, which significantly reduces the amount of tantalum, a rare resource, used, thereby significantly reducing costs.
[0054] The above is only a preferred embodiment of the present invention, and is not intended to limit the present invention. Those skilled in the art can make various modifications and changes to the present invention. All modifications, equivalent replacements, improvements, etc. made within the spirit and principle of the present invention should be included within the protection scope of the present invention.
Claims
1. a core made of one or more materials selected from the group consisting of niobium, zirconium, tungsten, molybdenum, titanium, nickel, iron, copper, aluminum, magnesium, cobalt, and alloys thereof; a tantalum metal layer covering an outer surface of the core; The material of the tantalum metal layer is a tantalum-niobium alloy, the tantalum content is greater than 50%, and the sum of the tantalum and niobium contents is greater than 95%; 1. A composite wire for an anode lead wire of a tantalum capacitor, comprising:
2. The cross section of the composite wire for the anode lead wire of the tantalum capacitor is circular, elliptical, or polygonal.
2. The composite wire for an anode lead of a tantalum capacitor according to claim 1.
3. the cross-sectional area of the tantalum metal layer occupies 1% to 80% of the cross-sectional area of the composite wire for an anode lead of a tantalum capacitor; 2. The composite wire for an anode lead of a tantalum capacitor according to claim 1.
4. the cross-sectional area of the tantalum metal layer occupies 1 to 50% of the cross-sectional area of the composite wire for an anode lead of a tantalum capacitor; 4. The composite wire for an anode lead of a tantalum capacitor according to claim 3.
5. The cross section of the composite wire is axially symmetric, with the longest axis being ≦3.0 mm and the shortest axis being ≧0.1 mm.
4. The composite wire for an anode lead of a tantalum capacitor according to claim 3.
6. A tantalum capacitor including an anode lead wire, the anode lead wire being manufactured using the composite wire for an anode lead wire of a tantalum capacitor according to any one of claims 1 to 5.
1. A tantalum capacitor comprising:
7. A method for producing the composite wire for an anode lead wire of a tantalum capacitor according to any one of claims 1 to 5, comprising the steps of: A step S1 of providing a core; and step S2 of coating the outer surface of the core with a tantalum metal layer to obtain a composite wire for an anode lead wire of the tantalum capacitor.
4. A method for producing a composite wire for an anode lead wire of a tantalum capacitor, comprising the steps of:
8. After S2, the method further includes a step of processing the composite wire for the anode lead wire of the tantalum capacitor into a required size by one or more processing methods selected from the group consisting of extrusion, rolling, rotary swaging, and drawing. The method according to claim 7 .
9. In the step S2, the outer surface of the core is coated with a tantalum metal layer by powder metallurgy, build-up welding, explosive bonding, pipe cladding, casting cladding or vapor deposition. The method according to claim 7 .
Citation Information
Patent Citations
For tantalum capacitor lead wire, the lead wire and the lead wire comprises a tantalum capacitor manufacturing method
JP1988502072A
High melting metal composite wire
JP1993228527A
Solid electrolytic capacitor electrode member and solid electrolytic capacitor using the same
JP2003272958A